Over the non-extensivity parameter for some superadditives systems (2010)
This article proposes a biunivocal relationship between the non-extensivity parameter q and the stationary probability density function f corresponding to an observable u for some super-additive systems in which the Tsallis Entropy is applicable. This relationship is given in terms of comparison between link functions that characterize the lack of memory of certain random variables associated with the parameter q and the stationary density f. Finally, from the previous results, a method is proposed that allows the parameter q to be approximated, by an estimate of f, when the effective energy associated with u is the effective kinetic energy.